Expressions of extracellular matrix‐remodeling factors in lymph nodes from oral cancer patients. (4th June 2020) - Fujita, Shuichi; Sumi, Misa; Tatsukawa, Eri; Nagano, Kenichi; Katase, Naoki
Abstract: Objective: Most malignant tumors require remodeling extracellular matrices (ECMs) for invasive growth and metastasis. Cancer cells and stromal cells remodel ECM. We investigated the relationship between regional lymph node (LN) metastasis and expression of ECM‐remodeling factors in oral squamous cell carcinoma (OSCC). Methods: Using primary OSCC and cervical LNs obtained surgically, we performed immunohistochemical evaluation of the ECM‐remodeling factors, lysyl oxidase (LOX), MT1‐MMP, S100A8, and TIMP‐1 in primary tumor and marginal sinus histiocytosis (MSH) in LNs, and determined the statistical significance of the positive rates between metastatic and metastasis‐free groups. Results: Marginal sinus histiocytosis was more frequently formed in the metastatic group compared to the metastasis‐free group. Lymphatic metastasis correlated with the immunopositivity rates of tumor cells expressing LOX, MT1‐MMP, and TIMP‐1, and of stromal cells expressing TIMP‐1. The case rates of MSH containing macrophages positive for LOX and MT1‐MMP in the metastasis group were significantly higher than in the metastasis‐free group. ECM‐remodeling‐associated macrophages accumulate in marginal sinus in conjunction with lymphatic metastasis. Conclusion: Expression of LOX, MT1‐MMP, and TIMP‐1 in the parenchyma, and stromal expression of TIMP‐1 in primary tumor may predict lymphatic metastasis. LOX and MT1‐MMP have a possibility to participate in formation of pre‐metastatic niche in LNs.